Dinamika Konflik Internal Gereja Akibat Mismanajemen Keuangan: Pendekatan Pastoral dalam Konstruksi Tata Kelola Keuangan - Andreas Kurniawan; Yonas Pasiran Ady Prayitno; Tjutjun Setiawan; Simon (Sekolah Tinggi Teologi Injili Indonesia Ambon, 2026)
The basis of this study is outlined by the researcher, starting from cases that occur in the field where conflicts arise within the church due to financial mismanagement. Ironically, the lack of accountability in church financial management has led to divisions and disputes in several churches. In analyzing this study, the researcher uses a qualitative method with a case study approach. This case study approach involves the researcher as an observer of the conflicts occurring in the church related to financial management aspects. The main research question posed by the researcher is how the construction of accountable church financial governance is implemented? The findings of this study explain that internal church conflicts are repeatedly triggered by financial issues. The model for constructing accountable church financial governance must be built on three main pillars: transparency, audit, and congregation participation. Without the integration of these three aspects, the construction effort will be partial and unsustainable.